Efecto de la siembra directa y trasplante con diferentes densidades de siembra sobre el crecimiento y rendimiento de quinua (Chenopodium quinoa Willd.) genotipo Tunkahuan, en La Argelia, Loja. - Armijos Armijos, Manuel Fabian (2023)
Quinoa (Chenopodium quinoa Willd.) is a crop of great importance worldwide for its high nutritional value. In Ecuador it is grown in the highlands, mainly in the provinces of Carchi, Cotopaxi and Pichincha, where yields of 1.38 t ha-1 have been recorded; however, Loja province is not a producer of quinoa. Within the cultural management, the method such as planting density are influential factors in production and that when used properly can increase yields. With this background, the objective of the present work was to evaluate the effect of direct seeding and transplanting with different planting densities on the growth and yield of quinoa. The experiment was carried out in "La Argelia Experimental Station" at the National University of Loja, which was established in plots with a completely randomized design (CRD) with a bifactorial arrangement with eight treatments and three replications. The planting methods studied were direct sowing and transplanting and the densities were 80,000, 100,000, 150,000 and 200,000 plants ha-1. During the crop cycle, the following variables were evaluated: crop phenology, height, diameter, chlorophyll content, leaf area index (LAI), biomass; the variables panicle weight, 1000 grain weight, number of grains plant-1, number of grains m-2, yield, biomass and harvest index when the crop reached physiological maturity. The following results were obtained: phenology with the transplanting method was delayed with 3 days, the best results for quantitative variables in growth were: height (224.51 cm) in the method by blow, diameter (1.97 cm), chlorophyll content (SPAD Index) (35.92) at the density of 80 000 plants ha-1, IAF (1.18), biomass (1624.52 g m-2) at the density of 200 000 plants ha-1; and panicle weight (120.23 g), number of grains plant-1 (21185) at the density of 80 000 plants ha-1, number of grains m-2 (235 415), yield (6.37 t ha-1) and biomass at the end of the crop cycle (2 414.44 g m-2) at the density of 200 000 plants ha-1; for the thousand-grain weight and harvest index, there were no significant differences in the yield variables. Finally, the results obtained show that the yield exceeded the national average, reaching a production of 6.37 t ha-1, with a very strong positive correlation with the number of grains m-2 r = 0.99 (<0.001). Keywords: Chenopodium quinoa, density, method, growth, yield.